The Effect of Ionic Liquid and Lithium Salt Electrolyte Addition on The Characteristics of Polyvinyl Alcohol/Chitosan-Based Membranes - Handika, Rudi Satya; Ratri, Christin Rina; Rohib, Rohib; Nugraha, Adam Febriyanto (BRIN Publishing (Penerbit BRIN), 2025)
The development of an environmentally friendly polymer electrolyte membrane for lithium-ion batteries is essential. A composite membrane composed of chitosan and polyvinyl alcohol (PVA) is one of the eco-friendly polymer membrane types used for lithium-ion battery electrolyte. This study examined the effect of ionic liquid 1-hexyl-3-methylimidazolium iodide (HMII) and lithium bis(oxalate) borate (LiBOB) electrolyte addition on the characteristics of composite membranes made of chitosan and PVA. The results reveal that the addition of LiBOB and HMII was able to promote the agglomerations and the formation of microcrystals, which increased the mechanical properties and ionic conductivities of the membranes. The membrane sample with LiBOB composition of 25% produced the highest mechanical properties with tensile strength of 21.11 MPa and elastic modulus of 1.93 MPa. The membrane sample with LiBOB composition of 10% without the addition of HMII produced the highest ionic conductivity, namely 5.17 x 10-6 S/cm.